Comparing cytocompatibility of two fluoride-containing solutions and two resin-based restorative materials—a pilot study - Mulder, Riaan; Noordien, Naeemah; Potgieter, Nicoline (Frontiers in Oral Health, 2024)
The cytocompatibility should always be considered, especially if the surface of the treated carious lesions is close to soft tissue or accidental exposure to the tissues by the clinician. Methods: This study aimed to compare the cytocompatibility of two fluoridecontaining liquids and two resin-containing restorative materials with buccal mucosa fibroblasts. The fluoride-containing materials were Silver Diamine Fluoride (SDF) and Water Based Silver Fluoride (AgF). Results: The statistical analysis was completed by comparing the positive control growth of the buccal mucosa fibroblasts to the growth of cells exposed to various materials. The one-way ANOVA with Tukey HSD result was completed. All the assessed materials compared to the control wells for both the 24 and 48 hour time intervals indicated a significant cytocompatibility result, except for the test wells with Stela (SDI) at the 24 hour time interval. No significant difference between the Step 2 liquids and the two dental materials in cytocompatibility was present at the 24 hour interval. All four materials indicated no significant differences between the cytocompatibility of any dental materials for 48 hours.The cytocompatibility assessment for Riva Star and Riva Star Aqua with the direct method in a full dispensing drop is not viable for Step 1 of the fluoride-containing liquids. The use of Stela Light Cure is a suitable material that will be in contact with buccal mucosa as it showed potential for increased cytocompatibility compared to Riva Light Cure. Riva Star Aqua is more cytocompatible than Riva Star.